Promosi Perpustakaan Melalui Media Sosial sebagai Upaya Peningkatan Minat Kunjung Pemustaka - Sarip, Ajeng Inten Legi Novita; Ilahi, Tarlina Nur; Rahmatullah, Tansah (Nusantara Journal of Information and Library Studies (N-JILS), 2024)
This research was titled "Library Promotion Through Social Media as an Effort to Increase Visitor Interest at the MTs Al-Mukhtariyah Rajamandala Library." The purpose of this study was to explore the promotion strategies carried out by the library through social media platforms and to analyze their impact on increasing visitor interest. In the digital era, social media became an essential tool for libraries to reach a wider audience and engage with the community. The research used a descriptive qualitative method, which allowed the researcher to gain deeper insights into the interactions and communication between the library and its users. The findings showed that well-planned and effective promotion increased public awareness of the library's existence, services, and collections. However, there were challenges in implementing promotions, such as limited human resources and inadequate digital infrastructure. Therefore, it was recommended that library managers develop more innovative and collaborative promotion strategies and optimize technology to increase visitor interest. Thus, this study was expected to contribute to the development of more effective library promotion practices in an educational context.